Anatomic and surgical study of the equine transverse colon from left paralombar aprouch - Van de Graaf, Guilherme Maia Mulder; Corrêa, Rodrigo Romero; Silva, Luis Cláudio Lopes Correia da; Zoppa, André Luis do Valle de (Brazilian Journal of Veterinary Research and Animal Science, 2007)
The transverse colon is a constriction of the bowel lumen, which can be submitted to obstructive process. The knowledge enlargement about this structure and the adjacent ones has a great surgical importance. For such study, ten anatomic pieces, from equines corpses of different breed, age and sex, were used and divided in two groups. In the first group an incision was made in the left 16 intercostal space and farther resection of the 16 rib. In the second group an incision was made over the 17 rib, before its ressection. All the identified structures were registered into individual files, such as the extension of the exteriorized portion. In all of the studied pieces, the transverse colon was entirely visualized and partially exteriorized. However, we had better handling and exteriorization in the second group, as well as we noticed its technique was of easier execution. In accordance with the results, through this work is possible to conclude that the transverse colon can be approached by the left flank, and that the removal of the 17 rib provides a better access to the transverse colon.